First-line treatment in the management of advanced renal cell carcinoma: systematic review and network meta-analysis. (August 2015) - Larkin, James; Paine, Abby; Foley, Grace; Mitchell, Stephen; Chen, Connie
<x xml:space="preserve">Abstract</x> Objectives: To conduct a systematic review and network meta-analysis (NMA) to assess effectiveness of first-line treatments for advanced renal cell carcinoma (RCC). Methods: Database searches were conducted to identify randomized controlled trials (RCTs) reporting results for eligible treatments. A fixed-effect Bayesian NMA was conducted to assess the relative effectiveness of treatments, with progression-free survival (PFS) reported as hazard ratios (HRs) and 95% credible intervals (CrIs). Results: Eleven unique RCTs were suitable for inclusion in the NMA. In the base case, in terms of PFS, sunitinib was superior compared with bevacizumab + IFN-α (HR = 0.79, 95% CrI: 0.64 – 0.96), everolimus (HR = 0.70, 95% CrI: 0.56 – 0.87), sorafenib (HR = 0.56, 95% CrI: 0.40 – 0.77) and temsirolimus + bevacizumab (HR = 0.74, 95% CrI: 0.56 – 0.96). Although, the point values for the mean and median HRs were < 1.0, there was no significant difference in PFS between sunitinib and axitinib, pazopanib or tivozanib. Although sensitivity analyses impacted the results of the NMA, no treatment was significantly more efficacious than sunitinib. Conclusion: Results from this analysis suggest that there is no treatment superior to the current benchmark treatment, sunitinib, in the management of advanced RCC in the first-line setting.